(untitled) (Journal of Bangladesh Institute of Planners, 2016)
Riverbank erosion is one of the major natural disasters in Bangladesh causing enormous and long term socio-economic consequences. Every year, approximately one million people are affected by river bank erosion. River bank erosion not only compels people to migrate or leave their place of origin, but also destroys their belongings. This research is conducted to analyze the river bank erosion scenario of Teota Union in Shibalaya Upazila of Manikgonj District located on the left bank of Jamuna River and also to analyze migration patterns. Teota union is the most vulnerable for river bank erosion due to char formation, shifting channels, and erosion. The amount of eroded and accreted areas of the study area in different periods from 1988 to 2014 has been computed from the satellite images of different years using GIS. During 1988-2014, the maximum bank erosion was occurred during 1988- 1990 and 2606.22 acres of land was eroded during that period and the minimum amount of land (995.12 acres) was eroded during 2005-2010 in the study area. JBIP, Vol. 9, 2016 (Printed in April 2018), pp. 81-93